Bis‐Diketopyrrolopyrrole and Carbazole‐Based Terpolymer for High Performance Organic Field‐Effect Transistors and Infra‐Red Photodiodes. Issue 17 (11th August 2019) - Opoku, Henry; Lim, Bogyu; Shin, Eun‐Sol; Kong, Hoyoul; Park, Jong Mok; Bathula, Chinna; Noh, Yong‐Young
Abstract: Carbazoles constitute one of the most widely used donor moieties for organic semiconductors due to their excellent hole transport and high environmental stability. However, they are seldomly used in recent high performance donor–acceptor (D–A) copolymers. In the present study, a planar regular terpolymer, PCbisDPP, composed of carbazole and thiophene flanked bis‐diketopyrrolopyrrole (bis‐DPP) for application as an active layer for high‐performance organic devices is reported. Organic field‐effect transistors with PCbisDPP as the active layer exhibit field‐effect mobility up to 1.48 cm 2 v −1 s −1, which to the best of the current knowledge corresponds to the highest hole mobility reported to date for carbazole‐based D–A polymers. The high mobility is achieved via a tailored polymer‐design resulting in high crystallinity and a strong aggregating property without sacrificing solubility. PCbisDPP is applied as an active donor material in organic photodiode with fullerene derivative PC61 BM as an acceptor in a bulk heterojunction blend. Binary additive combinations (tetralin: 1, 8‐diiodooxtane (3:3) v/v%) utilization achieves an impressive performance with an external quantum efficiency of 80%, an average responsivity of 309.1 mA W −1, and specific detectivity of 4.73 × 10 11 Jones in the near infra‐red light region (730 nm) utilizing a simple single layer organic photodiode structure as ITO/PEDOT:PSS/PCbisDPP:PC61 BM/LiF/Al. Abstract : Herein, a highly planar regular terpolymer, PCbisDPP, structurally composed of a carbazole and bis‐diketopyrrolopyrrole with thiophenes is reported for application as an active layer in high‐performance organic field effect transistors with a very high field effect mobility up to 1.48 cm 2 V −1 s −1, and organic photodiode with an external quantum efficiency of 80% at infra‐red light region (730 nm).